Resistance priming to enhance neuromuscular performance in Sport: Evidence, potential mechanisms and directions for future research - Harrison, P. W.; Lachlan, P.; McGuigan, M. R.; Jenkins, D. G.; Kelly, V. G. (Sports Medicine, 2019)
Recent scientific evidence supports the use of a low-volume strength-power `resistance priming` session prior to sporting competition in an effort to enhance neuromuscular performance. Though research evidence relating to this strategy is presently limited, it has been shown to be effective in improving various measures of neuromuscular performance within 48 h. Post-activation potentiation strategies have previously been shown to enhance strength-power performance within 20 min of completing maximal or near-maximal resistance exercise. Comparably, a delayed potentiation effect has been demonstrated following `resistance priming` at various times between 1 and 48 h in upper- and lower-body performance measures. This may have significant implications for a range of athletes when preparing for competition. Various exercise protocols have been shown to improve upper- and lower-body neuromuscular performance measures in this period. In particular, high-intensity resistance exercise through high loading (= 85% 1 repetition maximum) or ballistic exercise at lower loads appears to be an effective stimulus for this strategy. Although current research has identified the benefits of resistance priming to some physical qualities, many questions remain over the application of this type of session, as well as the effects that it may have on a range of specific sporting activities. The aims of this brief review are to assess the current literature examining the acute effects (1-48 h) of resistance exercise on neuromuscular performance and discuss potential mechanisms of action as well as provide directions for future research. Volltext siehe auch: ttps://www.researchgate.net/publication/333804244_Resistance_Priming_to_Enhance_Neuromuscular_Performance_in_Sport_Evidence_Potential_Mechanisms_and_Directions_for_Future_Research